2015
DOI: 10.4155/fmc.15.160
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel FFA4 (GPR120) Receptor Agonists with β-Arrestin2-Biased Characteristics

Abstract: These compounds may serve as the useful toolkits for detecting differential biased mechanism and developing new candidate therapeutic agents of the FFA4 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Different signaling pathways in different cell types were demonstrated with GW9508 and TUG-891 that recruited β-arrestin-2 in Caco-2 cells but not in STC-1 cells [ 43 ]. However, to fully elucidate the biological function of GPR120, the generation of selective biased agonists and assessment of signaling in different cell types are critical [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different signaling pathways in different cell types were demonstrated with GW9508 and TUG-891 that recruited β-arrestin-2 in Caco-2 cells but not in STC-1 cells [ 43 ]. However, to fully elucidate the biological function of GPR120, the generation of selective biased agonists and assessment of signaling in different cell types are critical [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GPR120 likely has a typical mechanism of activation observed in many GPCRs of the rhodopsin family. The validated GPR120 binding site, together with the improved homology model, could be further used for establishing the binding properties of a recently identified antagonist (Sparks et al 2014) and biased agonist (Li et al 2015). For instance, by introducing modifications in the cholecystokinin 2 (CCK2) receptor as well as in its biased antagonist suggested by modelling, Magnan and colleagues (Magnan et al 2013) were able to identify the key moiety in the ligand responsible for biased signalling and a microswitch of activation, involving M3.32 and Y7.43 that stabilizes the β-arrestin active state of the CCK2 receptor.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…A recent study has demonstrated that eicosapentaenoic acid can prevent arterial calcification via GPR120 in klotho mutant mice (13). In addition, some small molecules have been found to activate the GPR120 receptor with an excellent activity (14).…”
mentioning
confidence: 99%